2010
DOI: 10.1002/aic.12188
|View full text |Cite
|
Sign up to set email alerts
|

Study on factors influencing stagnation point offset of turbulent opposed jets

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Turbulent opposed jets were experimentally studied by the hot-wire anemometer measurement, the smoke-wire flow visualization, and the CFD simulation at L ¼ 1À20D (where L is the nozzle separation and D is the nozzle diameter) and Re [ 4500. The instability pattern of turbulent opposed jets was identified by investigating the smoke-wire photos recorded by a high-speed camera. The factors affecting stagnation point offset, such as the bulk velocity, the velocity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 27 publications
2
21
1
1
Order By: Relevance
“…Similarly, the stagnation point is also very sensitive to the little difference of the exit velocities of the opposed jets at 2 L/D 8, just as the conclusions reported in our previous work. 10,11 It can be seen from our previous studies [10][11][12] and current experimental results that both the stagnation point offset and the oscillation of the impingement plane are essentially caused by the exit velocity difference or fluctuations of the opposed jets. The exit velocity imbalance of opposed jets results in the stagnation point offset, while the periodic fluctuation exit velocity causes the axial periodic oscillation, and the oscillation frequency is almost equal to the excitation frequency.…”
Section: Dx5mentioning
confidence: 68%
See 1 more Smart Citation
“…Similarly, the stagnation point is also very sensitive to the little difference of the exit velocities of the opposed jets at 2 L/D 8, just as the conclusions reported in our previous work. 10,11 It can be seen from our previous studies [10][11][12] and current experimental results that both the stagnation point offset and the oscillation of the impingement plane are essentially caused by the exit velocity difference or fluctuations of the opposed jets. The exit velocity imbalance of opposed jets results in the stagnation point offset, while the periodic fluctuation exit velocity causes the axial periodic oscillation, and the oscillation frequency is almost equal to the excitation frequency.…”
Section: Dx5mentioning
confidence: 68%
“…[3][4][5][6][7][8][9] The stagnation point offset of turbulent opposed jets has been extensively studied in our previous study. [10][11][12] We have found that there exists a range of 2D L 8D, in which the stagnation point is very sensitive to the exit velocity ratio of the opposed jets. Simulations and bifurcation analyses of the structure and stability show that laminar axisymmetric opposed jets exhibit three steady states (two stable steady states and one unstable steady state) about at Re > 60, and no oscillatory instabilities were reported.…”
Section: Introductionmentioning
confidence: 86%
“…14,28 Occasionally, the impingement plane oscillates irregularly along the x-axis. The time series of locations of the impingement planes during the horizontal oscillation were analyzed using Image J from the recorded smoke images.…”
Section: B Horizontal Instability Of Planar Opposed Jetsmentioning
confidence: 99%
“…In such impinging-jets reactors, the flow regime plays a dominant role in determining the mixing and transfer efficiency. In last two decades, many fundamental studies on the dynamic characteristics of axisymmetric opposed jets have been carried out experimentally [9][10][11][12][13][14][15] or numerically. 16,17 Compared with axisymmetric opposed jets, planar opposed jets attach very little attention, but maybe have more potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…As for the axisymmetric opposed jets, multiple steady states of impinging plane in closely spaced axisymmetric opposed jets have been found by experimental way [6,7] and numerical way [3]. Li et al [4,8,9] experimentally studied the dynamic behavior of the impinging plane and found the phenomena of axial quasi-periodic oscillation of impinging plane and stagnation point offsets when L/D varied. The complex turbulent characteristic in impinging zone has also been widely studied [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%